1993
DOI: 10.1002/aja.1001960304
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for compartmental identity in the development of the rat lateral gastrocnemius muscle

Abstract: In adult rats, each neuromuscular compartment of the lateral gastrocnemius muscle (LG) is exclusively innervated by a primary branch of the LG nerve. In neonates, however, a small percentage of LG cells receives inputs from more than one primary nerve branch; these inputs are known as cross-compartmental. Cross-compartmental inputs are normally lost from the medial compartment of LG (LGm) by the 8th postnatal day. To investigate the mechanisms involved in the elimination of cross-compartmental inputs, muscle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…3a–b). This observation, however, is in agreement with other observations in which sprouts fail to extend into denervated regions from fully innervated muscle (Gatesy and English, 1993). In addition, there was little if any sprouting across the dorsal midline after a unilateral transaction of the LTN (supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…3a–b). This observation, however, is in agreement with other observations in which sprouts fail to extend into denervated regions from fully innervated muscle (Gatesy and English, 1993). In addition, there was little if any sprouting across the dorsal midline after a unilateral transaction of the LTN (supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…This degree of compactness of innervation is much greater than has been reported in either frog ( Trussell and Grinnell, 1985) or mammalian muscle (Gates and Betz, 1993;Smits et al, 1994). Muscles with multiple tendons or broad insertions, such as the frog gluteus (Bennett and Lavidis,198 I ) and the mammalian intercostal (Dennis and Harris, 1980), gluteal (Brown and Booth, 1983;English, 1990), lateral gastrocnemius (Gatesy and English, 1993), and masseter muscles (Weijs et al, 1993 ), often show motor unit localization within smaller muscle compartments defined by the presence of different nerve branches. In the snake transversus abdominis, each segmental muscle often has only one or two fast twitch motor axons, plus a greater number of slow twitch and tonic fiber axons, innervating a total of about 100 muscle fibers.…”
Section: Uniformity Of Fiber Types In Single Motormentioning
confidence: 91%
“…This specificity mainly takes two forms: there is early preferential (but not exclusive) innervation of a consistent histochemical muscle fiber type (Thompson et al, 1984;madby and Jansen, 1990;Thompson et al, 1990;Betz et al, 1990;Nelson and Thompson, 1994); and a given pool of motoneurons projects selectively to a single appropriate muscle, or even muscle compartment, and the "erroneous" connections that are found outside this region early in development get eliminated during maturation ( Lance-Jones and Landmesser, 198 la,b;Brown and Booth, 1983;Bennett and Lavidis, 1984;Callaway et al, 1989;Bennett and Ho, 1988;English, 1990;Gatesy and English, 1993). Even after this refinement, however, motor units tend to be widely distributed across a muscle or muscle compartment, with extensive spatial overlap of motor units of the same physiological/ histochemical type.…”
Section: Introductionmentioning
confidence: 96%
“…; Arnold et al. ), as there is substantial evidence that different portions of a muscle can work heterogeneously to produce total muscle force (Gatesy & English, ). In cases where it was found that modelled muscles would pass through other anatomical landmarks (either bone, retinaculae or other muscles), either ‘via points’ or wrapping surfaces were used to constrain them to realistic paths of action (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…GM was represented here by three separate muscles [GM (dorsal), GM (middle) and GM (ventral)], to account for its broad origin on the iliac crest, while M. biceps femoris posterior (BFP) was also represented by three muscles [BFP (cranial), BFP (middle) and BFP (caudal)] due to its broad insertion on the lateral aspect of the fibula and adjacent fascia. This is common in musculoskeletal modelling (Delp et al 1990;van der Helm et al 1992;Arnold et al 2010), as there is substantial evidence that different portions of a muscle can work heterogeneously to produce total muscle force (Gatesy & English, 1993). In cases where it was found that modelled muscles would pass through other anatomical landmarks (either bone, retinaculae or other muscles), either 'via points' or wrapping surfaces were used to constrain them to realistic paths of action ( Fig.…”
Section: Dorsiflexionplantarflexionmentioning
confidence: 99%